ETNOMATEMATIKA PADA TRANSAKSI JUAL BELI OLEH PEDAGANG SAYUR ETNIS MADURA DI PASAR PURING SIANTAN - Umsiah Umsiah; Agung Hartoyo; Silvia Sayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract Mathematics is a form of culture having been integrated in all aspects of daily life. This study aimed :1) To describe the form of mathematics applied by the community ethnic Madura in Pontianak Utara, 2) To review and describe the use of math trade deal  conducted by vegetable seller ethnic Madura in market Puring Siantan. Descriptive method was used in this study. Some speakers researched 12 vegetable trader ethnic madura. Data collection used a technique direct communication in the form of interview to the source of information. The data used was observation and interview. The result showed that: 1. The transaction conducted by vegetable seller ethnic madura consisting of acquisition, merchandise the determination of the selling price, and rounding off; 2. A sum done by summing scores for the thousands of zeros; The reduction of activity happened to the consumer spending money , conducted using system counting up; multiplication done by multiplying the number of spending with the thousands and using multiplication gradually which then result of each phase totaled; The division of being done by means of dividing between the highest rate and also carried out the gradually.  Keywords: Ethnic Madura, Etnomatematika, Trading Activity, Vegetable Seller